Systems analysis of dynamic transcription factor activity identifies targets for treatment in Olaparib resistant cancer cells. Issue 9 (18th May 2017) - Decker, Joseph T.; Hobson, Eric C.; Zhang, Yining; Shin, Seungjin; Thomas, Alexandra L.; Jeruss, Jacqueline S.; Arnold, Kelly B.; Shea, Lonnie D.
ABSTRACT: The development of resistance to targeted therapeutics is a challenging issue for the treatment of cancer. Cancers that have mutations in BRCA, a DNA repair protein, have been treated with poly(ADP‐ribose) polymerase (PARP) inhibitors, which target a second DNA repair mechanism with the aim of inducing synthetic lethality. While these inhibitors have shown promise clinically, the development of resistance can limit their effectiveness as a therapy. This study investigated mechanisms of resistance in BRCA‐mutated cancer cells (HCC1937) to Olaparib (AZD2281) using TRACER, a technique for measuring dynamics of transcription factor (TF) activity in living cells. TF activity was monitored in the parental HCC1937 cell line and two distinct resistant cell lines, one with restored wild‐type BRCA1 and one with acquired resistance independent of BRCA1 for 48 h during treatment with Olaparib. Partial least squares discriminant analysis (PLSDA) was used to categorize the three cell types based on TF activity, and network analysis was used to investigate the mechanism of early response to Olaparib in the study cells. NOTCH signaling was identified as a common pathway linked to resistance in both Olaparib‐resistant cell types. Western blotting confirmed upregulation of NOTCH protein, and sensitivity to Olaparib was restored through co‐treatment with a gamma secretase inhibitor. The identification of NOTCH signaling as a common pathway contributing to PARP inhibitor resistance by TRACER indicates the efficacy of transcription factor dynamics in identifying targets for intervention in treatment‐resistant cancer and provides a new method for determining effective strategies for directed chemotherapy. Biotechnol. Bioeng. 2017;114: 2085–2095. © 2017 Wiley Periodicals, Inc. Abstract : Dynamic cell response to therapy is dependent on the sensitivity of the cells to treatment. In this work, a transcriptional activity cell array (TRACER) was used to measure transcription factor activity dynamics in BRCA‐mutated breast cancer cells during treatment with Olaparib. The dynamic measurements were used to both identify sensitive and resistant cells as well as suggest therapy to resensitize resistant cells.